PENDUGAAN KERAGAMAN GENETIK DAN HERITABILITAS JAGUNG HIBRIDA SILANG PUNCAK PADA PERLAKUAN CEKAMAN KEKERINGAN - A, Adriani (Informatika Pertanian, 2015)
Development of maize varieties tolerant to drought is very important to extensification program in dry maginal lands, especially outside Java. The research objective was to evaluate the agronomic performance, genetic variabilities and heritabilities of hybrid maize top crosses at Probolinggo and Gowa during dry season. A randomized complete block design with two replications was applied to each location. The combined analysis of variance showed that hybrid x location interaction was significant for harvesting date, corncob length, 1000 grain weight, and highly significant for flowering date, leaf curling, husk cover aspect, corncob aspect, plant harvested, weight of corncob harvested and grain yield. The genetic variance was considered broad for grain yield, weight of corncob harvested, shalling percentage, number of grain rows per corncob, and corncob aspect. Heritability values in combined location analysis were high for shalling percentage; medium for grain yield, weight of corncob harvested, shalling number of grain rows per corncob and corncob aspect; but for the other characteristics they were low. Low selection intensity (≥ 10%) can be applied in this generation (S2), but strong selection intensity (≥20%) can be applied in the next generation (≥S3).